The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/1028415x.2018.1470372
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption in Menière’s disease patients

Abstract: It is possible that alcohol consumption delays the age at onset of Menière's disease. A hypothetical explanation is the inhibitory effect of alcohol on hypothalamic production of vasopressin. A reduced release of this neurohormone would increase diuresis and decrease endolymphatic pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, a few previous studies suggested supportive evidence for the inverse association between alcohol consumption and MD. It was supposed that alcohol can delay the onset of MD by reducing vasopressin synthesis [ 23 ]. Alcohol inhibited vasopressin synthesis by inhibiting hypothalamic function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few previous studies suggested supportive evidence for the inverse association between alcohol consumption and MD. It was supposed that alcohol can delay the onset of MD by reducing vasopressin synthesis [ 23 ]. Alcohol inhibited vasopressin synthesis by inhibiting hypothalamic function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…No RCTs were found that included caffeine or alcohol, and only a few very recent studies were found that specifically included caffeine 211 or alcohol. 212 The caffeine study found that MD patients had a higher mean daily caffeine intake than control subjects or patients with vertigo from other causes.…”
Section: Dietary Modificationsmentioning
confidence: 99%
“…-inflammatory cytokine levels (TNF-α; IL-1β) Elevated neurotrophic factors (BDNF) Elevated anti-inflammatory cytokine levels (IL-10) (Müller et al 2017)DementiaMechanism unknown(Peters et al 2008;Paganini- Hill et al 2016; Yasar 2018) Chronic painCentral nervous system depressant effect(Scott et al 2018) Meniere's disease Mechanism unknown(Sánchez-Sellero et al 2018) …”
mentioning
confidence: 99%